Effect of vitamin supplementation of receiving diets on the performance of stressed beef calves - Lee, B.; Stuart, R.; Perryman, K.; Ridenour, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ration formulation for stressed beef calves needs careful consideration, since low feed intakes, rumen dysfunction, and various other health and management problems may influence nutrient intakes and requirements. Supplementation with Vitamin E and B-complex vitamins in starting and receiving diets appears to improve animal performance and health.
Keywords: Beef; Vitamin; Performance; Health